NUCHLEOPHILIC SUBSTITUTION REACTION OF CYANIDE AND METHOXYDE IONS TO QUATERNARY MANNICH BASE FROM VANILLIN - Bambang Purwono; Estiana E.P Daruningsih (Universitas Gadjah Mada, 2007)
The nucleophilic substitution reaction to quaternary Mannich base from vanillin has been investigated. Mannich reaction to vanillin was carried out by refluxing mixture of vanillin, formaldehyde and dimethyl amine. Quaternary ammonium halide salt was obtained from reaction of Mannich vanillin base with methyl iodide in THF solvents and yielded 93.28%. Nucleophilic substituion to the halide salts with cyanide nucleophile produced 4-hidroxy-3-methoxy-5-(cyano)methylbenzaldehyde in 54.39% yield, with methoxyde ion obtained 4-hidroxy- 3-methoxy-5-(methoxy)-methyl-benzaldehide in 67.80% yield. The nucleophilic substitution reaction showed that substituen of trimethylamino quaternary Mannich base can act as a good leaving on nucleophilic reaction substitutions.